# Thread: Harmonic Conjugates

1. ## Harmonic Conjugates

I have two problems, but I am struggling to put the pieces together.

First:

Let v be a harmonic conjugate of u. Show that -u is a harmonic conjugate of v.

Second:

Suppose that v is a harmonic conjugate of u and that u is a harmonic conjugate of v. Show that u and v must be constant functions.

Can some push me in the right direction?

Thanks in advance

2. Originally Posted by ginafara
Let v be a harmonic conjugate of u. Show that -u is a harmonic conjugate of v.
Saying the v be a harmonic conjugate of u means that the function f=u+iv satisfies the Cauchy-Riemann equations.
Thus we know that $u_x = v_y \,\& \,u_y = - v_x$.
If g=v+i(-u) does g satisfy the Cauchy-Riemann equations?

3. Originally Posted by ginafara
I have two problems, but I am struggling to put the pieces together.

First:

Let v be a harmonic conjugate of u. Show that -u is a harmonic conjugate of v.

Second:

Suppose that v is a harmonic conjugate of u and that u is a harmonic conjugate of v. Show that u and v must be constant functions.

Can some push me in the right direction?

Thanks in advance
First:

So you have $f(x, y) = u(x, y) + i v(x, y)$ is analytic.

You want to prove that $g(x, y) = v(x, y) - i u(x, y)$ is analytic .......

Note that $g(x, y) = -i [i v(x, y) + u(x, y)] = -i f(x, y).$

Therefore .....

------------------------------------------------------------------------------------------------

Second:

So you have $f(x, y) = u(x, y) + i v(x, y)$ and $g(x, y) = v(x, y) + i u(x, y)$ are analytic.

You want to prove that u and v are constants.

From Cauchy-Riemann relations:

f analytic:

$\frac{\partial u}{\partial x} = \frac{\partial v}{\partial y} \,$ and $\, \frac{\partial u}{\partial y} = -\frac{\partial v}{\partial x}$.

g analytic:

$\frac{\partial v}{\partial x} = \frac{\partial u}{\partial y} \,$ and $\, \frac{\partial v}{\partial y} = -\frac{\partial u}{\partial x}$.

Therefore:

$\frac{\partial u}{\partial x} = -\frac{\partial u}{\partial x} \,$ and $\frac{\partial u}{\partial y} = -\frac{\partial u}{\partial y} \,$.

It follows that u = constant.

$\frac{\partial v}{\partial x} = -\frac{\partial v}{\partial x} \,$ and $\frac{\partial v}{\partial y} = -\frac{\partial v}{\partial y} \,$.

It follows that v = constant.